A low‐cost field ventilator: An urgent global need. Issue 3 (5th August 2021) - Nachiappan, Nitish; Koo, Jung Moses; Chockalingam, Nachiappan; Scott, Timothy E
Abstract: Modern ventilators are increasingly compact and able to deliver a wide range of ventilator modes and sophisticated monitoring capabilities. However, the global availability of ventilators is woefully short of demand. Data on intensive care units (ICUs), a proxy measure for hospital ventilator capacity in low and middle‐income countries (LMIC's), suggest that capacity is extremely limited where it exists at all. In LMIC's, the four most common indications for mechanical ventilation (MV) in ICUs are post‐surgical care, sepsis, trauma, and maternal peripartum or neonatal complications. A significant majority of these cases can be managed with intervention involving a short course of MV. Widespread and timely access to MV can thus effectively be used to help patients in these settings and improve outcomes. This paper implores this need and highlights the requirements for a low‐cost ventilator or a respiratory support device.